THE RELEVANCES OF JUSTICE VALUE TO LEGAL PROTECTION FOR GOODS AND SERVICE PROVIDERS IN CORRUPTION CASES - Maryanto Maryanto (UNISSULA, 2022)
The pace of infrastructure development in Indonesia is increasing rapidly, this is a form of the government's commitment to improving people's welfare. The pace of infrastructure development in reality often has problems, including failure to build. The absence of criminal provisions in Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods and Services has resulted in the blurring of the boundaries of the criminal and civil realms as well as administrative law in setting sanctions for providers of goods and services deemed negligent. This is often seen in cases of corruption in the procurement of goods and services, which often attracts service providers to become one of the perpetrators of criminal acts. This situation is clearly wrong, because not all acts of service and goods providers can be said to be related to the occurrence of corruption in the procurement of goods and services. This study aims to further analyze the legal protection for service and goods providers in cases of corruption in the procurement of goods and services. The method in this writing is normative. Based on the existing studies, it can be seen that the implementation of criminal sanctions for corruption in the procurement of goods for infrastructure development has not been based on the legal politics of procurement of goods, so that the criminal sanctions are still unclear, because the issue of procurement of goods should not be directly subject to criminal sanctions as an ultimum remidium, considering the procurement of goods regulated by administrative law not criminal law, while criminal threats are only as a last resort when violations in the realm of procurement of goods in infrastructure development are not controlled.